Event-triggered Data-efficient Observers of Perturbed Systems⁎This paper was elaborated in the UCoCoS project which has received funding from the European Union's Horizon 2020 research and innovation programme under the Marie Skłodowska-Curie grant agreement No 675080. Issue 2 (2020) - Voortman, Quentin; Efimov, Denis; Pogromsky, Alexander; Richard, Jean-Pierre; Nijmeijer, Henk
Abstract: In this paper, an event-triggered, data-rate constrained observer for discrete-time linear systems with perturbations is presented. The system is connected to a remote location by a communication channel which can only transmit limited numbers of bits per time interval. The system is subject to perturbations in its state as well as errors in the output measurement. The objective is to reconstruct estimates of the state at the remote location, by sending messages over the communication channel. A new type of data-rate constrained observer which can be more efficient in terms of communication rate is presented. Relation between an admissible communication rate and the system parameters is evaluated. The observer's efficiency is illustrated by simulations.